Hadis Sebagai Landasan Manajemen Pendidikan Islam - Amelia Suciyanti; Maya Fadillah; Intan Maulidia Fajri; Dwi Meutia Hasni4 (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study explores the management of Islamic education grounded in relevant Hadiths. As the second primary source of guidance for Muslims, the teachings of Prophet Muhammad (peace be upon him) should be actively applied by believers. The research highlights key aspects of Islamic education management, examining how Hadiths provide a framework for effective implementation, organization, execution, and evaluation, along with fundamental principles in this field. Through qualitative methodology and literature review, the study identifies four core concepts of Islamic education management: planning, organizing, actuating, and evaluating. Additionally, it outlines essential principles such as justice, sincerity, trustworthiness, honesty, and the promotion of good while preventing evil (*amar ma’ruf nahi munkar*). Practical applications include leadership, human resource management, learning management, and educational assessment—all supported by relevant Hadiths of the Prophet (ﷺ) to reinforce their validity and effectiveness.